2006
DOI: 10.1093/nar/gkl470
|View full text |Cite
|
Sign up to set email alerts
|

An RNA aptamer that interferes with the DNA binding of the HSF transcription activator

Abstract: Heat shock factor (HSF) is a conserved and highly potent transcription activator. It is involved in a wide variety of important biological processes including the stress response and specific steps in normal development. Reagents that interfere with HSF function would be useful for both basic studies and practical applications. We selected an RNA aptamer that binds to HSF with high specificity. Deletion analysis defined the minimal binding motif of this aptamer to be two stems and one stem–loop joined by a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 23 publications
1
52
0
Order By: Relevance
“…The prototypical example is the Xenopus transcription factor TFIIIA . When DNA-binding proteins are the target of RNA selection, the DNA-binding domain tends to be included in the preferred RNA binding site (Lebruska and Maher 1999;Cassiday and Maher 2001;Huang et al 2003;Choi et al 2006;Zhao et al 2006). Thus, transcription factors implicated in disease pathogenesis may be exploited for the development of therapeutic nucleic acid inhibitors such as RNA aptamers.…”
Section: Summary and Future Prospectsmentioning
confidence: 99%
“…The prototypical example is the Xenopus transcription factor TFIIIA . When DNA-binding proteins are the target of RNA selection, the DNA-binding domain tends to be included in the preferred RNA binding site (Lebruska and Maher 1999;Cassiday and Maher 2001;Huang et al 2003;Choi et al 2006;Zhao et al 2006). Thus, transcription factors implicated in disease pathogenesis may be exploited for the development of therapeutic nucleic acid inhibitors such as RNA aptamers.…”
Section: Summary and Future Prospectsmentioning
confidence: 99%
“…As demonstrated by us and others, RNA aptamers can be a powerful means to modulate transcription factors (Lebruska and Maher, 1999;Fan et al, 2004;Zhao et al, 2006). While most previously characterized RNA aptamers to DNAbinding proteins were found to recognize the DNA-binding surface of the targeted proteins, the aptamers we have selected and characterized here for ERa did not follow this pattern.…”
Section: Discussionmentioning
confidence: 81%
“…Several aptamers isolated previously for transcription factors were shown to interact with their target protein through the DNA binding site or domain and compete with the cognate DNA for binding (Lebruska and Maher, 1999;Fan et al, 2004;Zhao et al, 2006). But this was not the case for AptER-1, whose binding to ERa was not affected by the presence of 8,000-fold of ERE ( Fig.…”
Section: Rna Aptamers Bind Er With High Affinitymentioning
confidence: 92%
“…First, aptamers can be displaced by RNA constructs that mimic the viral panhandle structure (23), which is widely believed to be a recognition element for N. Second, many of the aptamers selected in the original study have sequences that resemble portions of the RVFV genome or antigenome by BLAST analysis (23). Finally, a survey of aptamer selections against diverse nucleic acid binding proteins demonstrated that aptamers invariably bound to the bona fide nucleic acid binding region of the protein unless deliberate steps were taken to prevent aptamer binding there (24)(25)(26).…”
mentioning
confidence: 99%